Thermal performance evaluation of a helically-micro-grooved heat pipe working with water and aqueous Al2O3 nanofluid at different inclination angle and filling ratio. (5th January 2017) - Aly, Wael I.A.; Elbalshouny, Moustafa A.; Abd El-Hameed, H.M.; Fatouh, M.
Highlights: Thermal performance of MGHP using Al2 O3 nanofluid is investigated. Inclination angle and filling ratio are affecting the HP thermal performance. An inclination angle of 60° exhibits the best performance. Evaporation and condensation HTC increase by up to 30.4% and 11.1%. Thermal resistance decreases by up to 18.2%. Abstract: The present work reports the thermal performance of a helically-micro-grooved heat pipe working with water-based alumina nanofluid. The effects of the inclination angle (0°, 30°, 60° and 90°), filling ratio (20, 40, 60 and 80%) and heat input (45:65 W) on heat transfer characteristics of the heat pipe using either distilled water or water-based alumina nanofluid with the volume concentration of Al2 O3 nanoparticles of 3.0% are experimentally investigated. Results revealed that the thermal performance of the heat pipe enhances with nanofluid compared to DW and both inclination angle and filling ratio significantly affect the thermal performance of the heat pipe. The evaporation and condensation heat transfer coefficients increase as filling ratio increases, but thermal resistance decreases when filling ratio increases. Moreover, the inclination angle of 60° achieves the best thermal performance of the heat pipe using water or nanofluid. The evaporation and condensation heat transfer coefficients of nanofluid are higher than those of water by 30.4% and 11.1%, respectively, while the thermal resistance of nanofluid is lower than that of water by about 18.2%.